Pendidikan Islam memandang stratifikasi sosial dalam masyarakat - Kusuma Listiani, Salma; khasanah, nur (Jurnal Pendidikan Agama Islam, 2025)
Society is a group of individuals from various backgrounds who live together under shared norms and binding rules. In social life, differences in economic, political, and cultural aspects give rise to unavoidable social stratification. This phenomenon leads to competition among individuals to obtain social status. From an Islamic perspective, all humans are created by Allah SWT with equal dignity and status. However, in reality, social inequality still exists and needs to be examined from the perspective of Islamic education. Islamic education plays a crucial role in instilling the values of equality, justice, and humanity, as well as serving as a means to mitigate the negative impacts of social stratification. This study employs a qualitative research method with a literature review approach. Social stratification refers to the hierarchical layering of society based on power, wealth, honor, and knowledge, which forms upper, middle, and lower classes. Education is a significant factor in shaping social stratification. In Islam, there is no concept of social stratification, as Islam emphasizes that all humans are equal, and the only distinction among them lies in their level of piety. Islamic education does not view humans merely from a physical perspective but also from a spiritual dimension, through which Islamic teachings shape both individual piety and social morality.